'Nevi of Ota: the unusual birthmarks': a case review. (1st March 2013) - Mohan, Ravi Prakash Sasankoti; Verma, Sankalp; Singh, Amit Kumar; Singh, Udita
Abstract : Nevi of Ota are usually characterised by unilateral, mottled, slate blue or dark brown macules on the forehead and face around the eye area. These are unusual skin discolorations in which melanocytes are found deeper than normal. Ota's nevus is usually congenital but may appear in early childhood or in puberty. We summarise a case report along with histological and management aspects of this cosmetically unappealing condition.